Characterizing the Posttransfer Period Among Patients with Pediatric Onset IBD: The Impact of Academic Versus Community Adult Care on Emergent Health Resource Utilization. Issue 9 (September 2017) - Bollegala, Natasha; Benchimol, Eric I.; Griffiths, Anne M.; Kovacs, Adrienne; Steinhart, Allan H.; Zhao, Xinbei; Nguyen, Geoffrey C.
Abstract : Background: Patients diagnosed with inflammatory bowel disease (IBD) during childhood require transfer to an adult gastroenterologist, in Ontario usually just before their 18th birthday. Pediatric onset IBD is a complex phenotype with demonstrated noncompliance risk that may require targeted measures to optimize health care outcomes in the adult care setting. Purpose: The purpose of this study was to determine the impact of posttransfer health care setting (academic versus community gastroenterologist) on emergent health resource utilization. Methods: This was a population-based retrospective cohort study using health care administrative data from Ontario, Canada. A cohort of patients with Pediatric onset IBD was identified and health resource utilization during a 2-year pretransfer period, transfer of care period and 2-year posttransfer period was analyzed. Posttransfer health care setting was defined as academic (i.e., gastroenterologists providing care in a university affiliated tertiary care center) versus community. A third comparator group, loss to follow-up, was also identified. The primary outcome of this study comprised emergency department utilization. Secondary outcomes included hospitalizations, surgeries, ambulatory visits, endoscopic investigations, and radiological investigations. Results: Overall, there were no significant differences found in emergency department use, ambulatory care visits (aside from the expected drop in the lost to follow-up group), hospitalizations, endoscopic procedures, or radiological procedures between exposure groups. Conclusions: Posttransfer health care setting does not seem to significantly impact emergent health resource utilization in the posttransfer period. Abstract : Article first published online 10 August 2017.